Detraining attenuation during the COVID-19 pandemic: practical considerations for home-based strength and power training - Guimarães-Ferreira, L.; Salles Bocalini, D. (Revista Brasileira de Fisiologia do Exercisio, 2020)
The COVID-19 pandemic that scattered across the world in 2020 has required collective action to control the transmission of the disease. Among the measures, social distancing has been widely adopted, aiming to reduce contact and people gathering. With the limited access to training places that have equipment and a variety of loads for strength and power training, alternative strategies to be carried out in the domestic environment are important for maintaining physical conditioning and mitigating the deleterious effects of detraining. Based on the available scientific literature, this article presents practical recommendations for strength training in the home environment. It is recommended to perform exercises that employ self-body weight, household items and, when available, dumbbells and elastic bands. Whenever using low loads (30-50% of 1 repetition maximum), performing the sets until the concentric failure seems to be necessary to optimize gains in strength and muscle mass. The practice of physical exercises should be performed on most days of the week (> 5 days/week), combined with domestic and leisure activities that involve the movement of the whole body. For maintenance and / or development of muscle power, ballistic movements must be included, in the presence or absence of external loads.